A sandwich pressure sensor and its preparation method
By adopting a sandwich structure in the flexible pressure sensor, using a natural latex sponge layer and a carbon nanotube/epoxidized natural rubber conductive film, the problem of difficulty in balancing sensitivity and stability in the prior art is solved, and high sensitivity, wide working range and good fatigue resistance are achieved.
Patent Information
- Application Number
- CN202410097880.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-01-24
AI Technical Summary
Existing flexible pressure sensors are difficult to balance in terms of sensitivity, working range, linearity and stability, and the preparation process is complex, making it difficult to achieve large-scale production.
It adopts a sandwich structure, including two upper and lower natural latex sponge layers and a strain layer located between the two layers. The strain layer is composed of a conductive film made of carbon nanotubes and epoxidized natural rubber.
It has achieved high flexibility, stability and wide working range, good sensitivity and good fatigue resistance, and is suitable for motion sensing and health monitoring and other fields.
Smart Images

Figure CN117968901B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flexible pressure sensors, and in particular to a sandwich pressure sensor and a preparation method thereof. Background Art
[0002] With the rapid development of science and technology, the working environment is becoming more and more diverse and complex. Traditional metal or inorganic semiconductor sensors can no longer meet people's needs. Flexible pressure sensors are highly sensitive and small-sized sensing devices that can sense small-range pressures, monitor deformations, and convert them into electrical signals. They are now widely used in wearable electronics, human-computer interaction interfaces, biological signal monitoring and other industries with broad prospects.
[0003] At present, there are three main preparation processes for flexible pressure sensors: filling type, adsorption type and sandwich type. The filling type is to disperse a high content of conductive filler in an insulating polymer base material to prepare a flexible strain sensor, which will result in a high Young's modulus, low flexibility and high cost of the strain sensor. At the same time, the content of the conductor and the morphology design of the composite conductor need to be precisely controlled during the preparation process, making it difficult to achieve large-scale production; the flexible strain sensor prepared by the adsorption type forms a conductive film on the surface of the polymer base material through transfer, immersion, deposition and other methods. The operation is simple, but the simple surface adsorption causes the bonding between the conductive layer and the elastic base to decrease with the increase in the number of uses, which will affect the long-term performance of the device.
[0004] The sandwich flexible strain sensor uses screen printing, transfer printing, layered coating and other processes to make a conductive layer on the surface of the polymer base material, and then encapsulates it with the polymer base material. It has high sensitivity and can monitor smaller strains. Compared with the process of co-doping the conductive active material with the elastic matrix to construct a composite structure, the sandwich structure based on the overlap of the conductive active material and the elastic matrix is simpler and more effective. It can reduce the amount of conductive active material while ensuring the conductive sensing performance, thereby achieving the purpose of cost saving. Moreover, from the perspective of industrial production, this method of preparing the sandwich conductive elastomer can better realize mass industrial production, thereby meeting the market demand for large-scale conductive elastomers. However, the overall performance parameters of the pressure sensor, namely sensitivity, working range, linearity and stability, are still difficult to balance. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a sandwich pressure sensor and a preparation method thereof.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0007] The invention discloses a sandwich pressure sensor, comprising upper and lower natural latex sponge layers and a strain layer located between the upper and lower natural latex sponge layers, wherein the strain layer is a conductive film mainly made of carbon nanotubes and epoxidized natural rubber.
[0008] Preferably, the carbon nanotubes are single-walled carbon nanotubes, and the epoxidation degree of the epoxidized natural rubber is 30 to 50 mol%.
[0009] Preferably, in parts by mass, the natural latex sponge layer includes 80-120 parts of natural latex, 2-5 parts of sulfur, 0.5-2 parts of 2-mercaptobenzothiazole, 0.2-1.5 parts of 2-mercaptobenzimidazole, 1-4 parts of potassium oleate, 2-5 parts of zinc oxide, 0.5-2 parts of potassium hydroxide and 0.5-2 parts of sodium fluorosilicate.
[0010] Accordingly, a method for preparing a sandwich pressure sensor comprises the following steps:
[0011] (1) After mixing the single-walled carbon nanotube dispersion and the epoxidized natural rubber latex, the mixture is shaken for 15 to 30 minutes and then injected into a mold to form a film to obtain a strained material, which is then spread on a natural latex sponge layer at a film-forming temperature of 40 to 65° C.;
[0012] (2) The conductive copper foil is pasted on the surface of the strain material, and the foamed latex is injected and spread on the conductive copper foil for sealing, and then shaped and vulcanized, and dried at 60° C. for 2 to 2.5 hours to obtain a sandwich pressure sensor.
[0013] Preferably, the mass ratio of the single-walled carbon nanotube dispersion to the epoxidized natural rubber is 1:1 to 1:100.
[0014] Preferably, the concentration of the single-walled carbon nanotube dispersion is 1-4 mg / ml; the concentration of the epoxidized natural rubber latex is 100-350 mg / ml.
[0015] Preferably, the preparation process of the natural latex sponge layer is: adding sulfur, 2-mercaptobenzothiazole, 2-mercaptobenzimidazole, and potassium hydroxide dispersion to natural latex, and aging to obtain a compound latex; mixing the compound latex, potassium oleate, zinc oxide, and sodium fluorosilicate to obtain a foamed latex; injecting the foamed latex into a mold, shaping and vulcanizing it, and preparing the natural latex sponge layer.
[0016] Preferably, in parts by weight, the natural latex sponge layer includes 80-120 parts of natural latex, 2-5 parts of sulfur, 0.5-2 parts of 2-mercaptobenzothiazole, 0.2-1.5 parts of 2-mercaptobenzimidazole, 1-4 parts of potassium oleate, 2-5 parts of zinc oxide, 0.5-2 parts of potassium hydroxide and 0.5-2 parts of sodium fluorosilicate.
[0017] Preferably, the aging temperature is 25° C. and the time is 24 to 48 hours; the shaping temperature is 80 to 90° C. and the time is 20 to 40 minutes; and the vulcanization temperature is 100° C. and the time is 15 to 25 minutes.
[0018] Preferably, the preparation process of the single-walled carbon nanotube dispersion is: weigh single-walled carbon nanotubes and sodium taurodeoxycholate in a mass ratio of 1:7-10, mix them with deionized water, place them in an ice water bath for ultrasonic dispersion for 10-20 minutes, filter out undispersed carbon nanotubes, and bottle them for later use.
[0019] The present invention has the following beneficial effects:
[0020] 1. The present invention draws on the "sandwich" structure to assemble a sandwich pressure sensor made of natural latex sponge as a flexible substrate and packaging layer, and a composite conductive film as a strain layer. The sensor is easy to prepare and has a simple process. It not only has high flexibility and high stability, but also has a wide working range, good sensitivity, and good fatigue resistance. It is expected to be used in motion sensing, health monitoring and other fields.
[0021] 2. The present invention is assembled with a natural latex sponge layer as a flexible base layer and encapsulation layer, and a carbon nanotube / epoxidized natural latex conductive film as a strain layer. In the composite strain layer, the carbon nanotubes provide more conductive paths for the film, and the addition of epoxidized natural latex also makes the formed conductive paths more stable, thereby achieving a more stable signal output; the natural latex foam sponge used has high flexibility and strong deformation ability under applied pressure, and can greatly reduce the loss of the strain layer during use, thereby improving the recycling rate of the sensor. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the preparation of the sandwich pressure sensor of the present invention;
[0023] Figure 2 This is a SEM electron microscope image of the cross section of the sandwich sponge sensor prepared by the present invention;
[0024] Figure 3 This is a SEM electron microscope image of the cross section of the carbon nanotube / epoxidized natural rubber strain layer prepared in Example 3;
[0025] Figure 4 This is a sensitivity test result diagram of the sandwich sponge sensor prepared in Example 3;
[0026] Figure 5 This is a step cycle test result diagram of the sandwich sponge sensor prepared in Example 3;
[0027] Figure 6This is a graph showing the cycle test results of the sandwich sponge sensor prepared in Example 3 under small deformation;
[0028] Figure 7 This is a graph showing the cyclic test results of the sandwich sponge sensor prepared in Example 3 under large deformation;
[0029] Figure 8 This is a graph showing the cyclic test results of the sandwich sponge sensor prepared in the comparative example under large deformation;
[0030] Fig. 9 This is a diagram showing the fatigue test results of the sandwich sponge sensor prepared in Example 3. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0033] 1. The present invention discloses a sandwich pressure sensor, comprising an upper and lower natural latex sponge layer as a flexible substrate and an encapsulation layer and a strain layer located between the upper and lower natural latex sponge layers, wherein the strain layer is a conductive film mainly made of carbon nanotubes and epoxidized natural rubber. The simple preparation process is as follows Figure 1 shown.
[0034] Furthermore, the carbon nanotubes are single-walled carbon nanotubes, and the epoxidation degree of the epoxidized natural rubber is 30 to 50 mol%.
[0035] Calculated by weight, the natural latex sponge layer includes 80-120 parts of natural latex, 2-5 parts of sulfur, 0.5-2 parts of 2-mercaptobenzothiazole, 0.2-1.5 parts of 2-mercaptobenzimidazole, 1-4 parts of potassium oleate, 2-5 parts of zinc oxide, 0.5-2 parts of potassium hydroxide and 0.5-2 parts of sodium fluorosilicate.
[0036] 2. The present invention discloses a method for preparing a sandwich pressure sensor, comprising the following steps:
[0037] (1) sulfur, 2-mercaptobenzothiazole, 2-mercaptobenzimidazole and potassium hydroxide dispersion are added to natural rubber latex and ripened to obtain a compound latex; the compound latex, potassium oleate, zinc oxide and sodium fluorosilicate are mixed to obtain a foaming latex.
[0038] (2) Injecting the foamed latex into a mold, shaping and vulcanizing it to prepare a natural latex sponge layer.
[0039] (3) After mixing the single-walled carbon nanotube dispersion and the epoxidized natural rubber latex, the mixture is shaken for 15 to 30 minutes and then injected into a mold to form a film to obtain a strain material, which is then spread on the natural latex sponge layer at a film-forming temperature of 40 to 65° C.;
[0040] (4) The conductive copper foil is pasted on the surface of the strain material, and the foamed latex is injected and spread on the conductive copper foil for sealing, and then shaped and vulcanized, and dried at 60° C. for 2 to 2.5 hours to obtain a sandwich pressure sensor.
[0041] The mass ratio of the single-walled carbon nanotube dispersion to the epoxidized natural rubber is 1:1 to 1:100. The concentration of the single-walled carbon nanotube dispersion is 1 to 4 mg / ml; and the concentration of the epoxidized natural rubber latex is 100 to 350 mg / ml.
[0042] Furthermore, in terms of weight parts, the natural latex sponge layer includes 80-120 parts of natural latex, 2-5 parts of sulfur, 0.5-2 parts of 2-mercaptobenzothiazole, 0.2-1.5 parts of 2-mercaptobenzimidazole, 1-4 parts of potassium oleate, 2-5 parts of zinc oxide, 0.5-2 parts of potassium hydroxide and 0.5-2 parts of sodium fluorosilicate.
[0043] Furthermore, the aging temperature is 25° C. and the time is 24 to 48 hours; the shaping temperature is 80 to 90° C. and the time is 20 to 40 minutes; and the vulcanization temperature is 100° C. and the time is 15 to 25 minutes.
[0044] Furthermore, the preparation process of the single-walled carbon nanotube dispersion is as follows: single-walled carbon nanotubes and sodium taurodeoxycholate are weighed in a mass ratio of 1:7 to 10 (preferably 1:9), mixed with deionized water, and then placed in an ice water bath for ultrasonic dispersion for 10 to 20 minutes, filtered to remove undispersed carbon nanotubes, and then bottled for later use.
[0045] The present invention will be further described below in conjunction with specific embodiments.
[0046] Example 1
[0047] A method for preparing a sandwich pressure sensor based on natural rubber composite nanomaterials comprises the following steps:
[0048] 1) Weigh 100 parts of concentrated natural rubber latex with a total solid content of 60% by mass, add a dispersion (50%) prepared by grinding 2.5 parts of sulfur, 1 part of 2-mercaptobenzothiazole, 0.75 parts of 2-mercaptobenzimidazole and 1 part of potassium hydroxide, stir evenly and mature at 25°C for 30 hours. Add 2 parts of potassium oleate and foam at high speed for 15 minutes, then foam at medium speed and add 2.5 parts of zinc oxide, stir for 5 minutes and then add 0.9 parts of sodium fluorosilicate.
[0049] 2) The foamed latex is injected into the mold, placed at 80° C. for shaping for 20 minutes, and then placed at 100° C. for vulcanization for 15 minutes to obtain a natural latex sponge layer.
[0050] 3) Take 0.02 ml of epoxidized natural rubber latex (250 mg / ml) and add it to 2.5 ml of single-walled carbon nanotube dispersion (2 mg / ml), wherein the mass ratio of single-walled carbon nanotube to epoxidized natural rubber latex is 1:1. After oscillating with an oscillator for 30 minutes, inject it into a mold and spread it on a flexible substrate, and place it at 60°C for hot air drying until it forms a film.
[0051] 4) Paste the conductive copper foil on the surface of the strain material, inject and spread the foamed latex that has reached the gel point, place it at 80°C for 20 minutes, and then place it at 100°C for vulcanization for 15 minutes to obtain a sandwich pressure sensor.
[0052] Example 2
[0053] A method for preparing a sandwich pressure sensor based on natural rubber composite nanomaterials comprises the following steps:
[0054] 1) Weigh 100 parts of concentrated natural rubber latex with a total solid content of 60% by mass, add a dispersion (50%) prepared by grinding 2.5 parts of sulfur, 1 part of 2-mercaptobenzothiazole, 0.75 parts of 2-mercaptobenzimidazole and 1 part of potassium hydroxide, stir evenly and mature at 25°C for 30 hours. Add 2 parts of potassium oleate and foam at high speed for 15 minutes, then foam at medium speed and add 2.5 parts of zinc oxide, stir for 5 minutes and then add 0.9 parts of sodium fluorosilicate.
[0055] 2) The foamed latex is injected into the mold, placed at 80° C. for shaping for 20 minutes, and then placed at 100° C. for vulcanization for 15 minutes to obtain a natural latex sponge layer.
[0056] 3) Take 0.1 ml of epoxidized natural rubber latex (250 mg / ml) and add it to 2.5 ml of single-walled carbon nanotube dispersion (2 mg / ml), wherein the mass ratio of single-walled carbon nanotube to epoxidized natural rubber is 1:5. After oscillating with an oscillator for 30 minutes, inject it into a mold and spread it on a flexible substrate, and place it at 60°C for hot air drying until it forms a film.
[0057] 4) Paste the conductive copper foil on the surface of the strain material, inject and spread the foamed latex that has reached the gel point, place it at 80°C for 20 minutes, and then place it at 100°C for vulcanization for 15 minutes to obtain a sandwich pressure sensor.
[0058] Example 3
[0059] A method for preparing a sandwich pressure sensor based on natural rubber composite nanomaterials comprises the following steps:
[0060] 1) Weigh 100 parts of concentrated natural rubber latex with a total solid content of 60% by mass, add a dispersion (50%) prepared by grinding 2.5 parts of sulfur, 1 part of 2-mercaptobenzothiazole, 0.75 parts of 2-mercaptobenzimidazole and 1 part of potassium hydroxide, stir evenly and mature at 25°C for 30 hours. Add 2 parts of potassium oleate and foam at high speed for 15 minutes, then foam at medium speed and add 2.5 parts of zinc oxide, stir for 5 minutes and then add 0.9 parts of sodium fluorosilicate.
[0061] 2) The foamed latex is injected into the mold, placed at 80° C. for shaping for 20 minutes, and then placed at 100° C. for vulcanization for 15 minutes to obtain a natural latex sponge layer.
[0062] 3) Take 0.2 ml of epoxidized natural rubber latex (250 mg / ml) and add it to 2.5 ml of single-walled carbon nanotube dispersion (2 mg / ml), wherein the mass ratio of single-walled carbon nanotube to epoxidized natural rubber is 1:10. After oscillating with an oscillator for 30 minutes, inject it into a mold and spread it on a flexible substrate, and place it at 60°C for hot air drying until it forms a film.
[0063] 4) Paste the conductive copper foil on the surface of the strain material, inject and spread the foamed latex that has reached the gel point, place it at 80°C for 20 minutes, and then place it at 100°C for vulcanization for 15 minutes to obtain a sandwich pressure sensor.
[0064] Example 4
[0065] A method for preparing a sandwich pressure sensor based on natural rubber composite nanomaterials comprises the following steps:
[0066] 1) Weigh 100 parts of concentrated natural rubber latex with a total solid content of 60% by mass, add a dispersion (50%) prepared by grinding 2.5 parts of sulfur, 1 part of 2-mercaptobenzothiazole, 0.75 parts of 2-mercaptobenzimidazole and 1 part of potassium hydroxide, stir evenly and mature at 25°C for 30 hours. Add 2 parts of potassium oleate and foam at high speed for 15 minutes, then foam at medium speed and add 2.5 parts of zinc oxide, stir for 5 minutes and then add 0.9 parts of sodium fluorosilicate.
[0067] 2) The foamed latex is injected into the mold, placed at 80° C. for shaping for 20 minutes, and then placed at 100° C. for vulcanization for 15 minutes to obtain a natural latex sponge layer.
[0068] 3) Take 1 ml of epoxidized natural rubber latex (250 mg / ml) and add it to 2.5 ml of single-walled carbon nanotube dispersion (2 mg / ml), wherein the mass ratio of single-walled carbon nanotube to epoxidized natural rubber is 1:50. After oscillating with an oscillator for 30 minutes, inject it into a mold and spread it on a flexible substrate, and place it at 60°C for hot air drying until it forms a film.
[0069] 4) Paste the conductive copper foil on the surface of the strain material, inject and spread the foamed latex that has reached the gel point, place it at 80°C for 20 minutes, and then place it at 100°C for vulcanization for 15 minutes to obtain a sandwich pressure sensor.
[0070] Example 5
[0071] A method for preparing a sandwich pressure sensor based on natural rubber composite nanomaterials comprises the following steps:
[0072] 1) Weigh 100 parts of concentrated natural rubber latex with a total solid content of 60% by mass, add a dispersion (50%) prepared by grinding 2.5 parts of sulfur, 1 part of 2-mercaptobenzothiazole, 0.75 parts of 2-mercaptobenzimidazole and 1 part of potassium hydroxide, stir evenly and mature at 25°C for 30 hours. Add 2 parts of potassium oleate and foam at high speed for 15 minutes, then foam at medium speed and add 2.5 parts of zinc oxide, stir for 5 minutes and then add 0.9 parts of sodium fluorosilicate.
[0073] 2) The foamed latex is injected into the mold, placed at 80° C. for shaping for 20 minutes, and then placed at 100° C. for vulcanization for 15 minutes to obtain a natural latex sponge layer.
[0074] 3) Take 2 ml of epoxidized natural rubber latex (250 mg / ml) and add it to 2.5 ml of single-walled carbon nanotube dispersion (2 mg / ml), wherein the mass ratio of single-walled carbon nanotube to epoxidized natural rubber is 1:100. After oscillating with an oscillator for 30 minutes, inject it into a mold and spread it on a flexible substrate, and place it at 60°C for hot air drying until it forms a film.
[0075] 4) Paste the conductive copper foil on the surface of the strain material, inject and spread the foamed latex that has reached the gel point, place it at 80°C for 20 minutes, and then place it at 100°C for vulcanization for 15 minutes to obtain a sandwich pressure sensor.
[0076] Comparative Example 1
[0077] Compared with Example 1, this comparative example does not add epoxidized natural rubber latex, and only takes 2.5 ml of single-walled carbon nanotube dispersion (2 mg / ml) for film laying, and the rest is the same.
[0078] The microscopic morphology of the cross-section of the prepared sandwich sponge sensor was observed using a scanning electron microscope. Figure 2 As shown, the upper and lower layers of the sensor are sponge layer structures, the middle layer is a carbon nanotube / epoxidized natural rubber composite conductive strain layer, and the three structures are tightly stacked to form a "sandwich" interlayer.
[0079] The microscopic morphology of the cross section of the carbon nanotube / epoxidized natural rubber strain layer prepared in Example 3 was observed using a scanning electron microscope. Figure 3 As shown, the filling of epoxidized natural rubber can make the carbon nanotubes form a stable conductive path, eliminating the influence of the stray peaks caused by the scattered distribution of carbon nanotubes in the sensing performance test.
[0080] The prepared sandwich sponge sensor was tested for various sensing properties using a tensile testing machine equipped with a 2000N force sensor and a digital multimeter. The results are as follows:
[0081] Figure 4 The working curve of the sandwich sponge sensor prepared in Example 3 in the range of 0-200 kPa is shown in the figure. The obtained curve is segmented and fitted to obtain the corresponding standard factor S of each segment, that is, the linear relationship between stress and resistance change. As shown in the figure, in the stress range of 0-20 kPa, S1=3.94×10 -3 kPa -1 ; In the stress range of 110-200 kPa, S2 = 1.78 × 10 -4 kPa -1 .
[0082] Figure 5 The step pressure loading and unloading curve of the sandwich sponge sensor prepared in Example 3 was subjected to pressure loading and unloading at deformations of 10%, 30%, 40%, 50% and 60%, respectively, and stayed at each deformation stage for 10 seconds. As shown in the figure, there was no delay in resistance recovery under continuous deformation, and stable operation was achieved.
[0083] Figure 6 and Figure 7 They are the working curves of the sandwich sponge sensor prepared in Example 3 after applying and releasing pressure 10 times under deformations of 5% and 50%. It can be seen from the figure that the sensor can work stably under small deformation and large deformation and has a wide working range.
[0084] Figure 8 This is the working curve of the sandwich sponge sensor prepared in Example 1 after applying and releasing pressure 10 times under a deformation of 50%. Compared with the composite strain layer, the working curve of the sensor assembled by the strain layer of pure carbon nanotubes has more impurities, indicating that the addition of epoxidized natural rubber latex can make the conductive path formed by the carbon nanotubes more stable, allowing the strain layer to achieve more stable signal transmission, thereby maintaining stable operation of the sensor.
[0085] like Fig. 9 As shown, after applying and releasing pressure 500 times, the sandwich sponge sensor prepared in Example 3 can still work stably and has good fatigue resistance.
[0086] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A sandwich pressure sensor, characterized in that: It comprises an upper and a lower natural latex sponge layer and a strain layer located between the upper and lower natural latex sponge layers, wherein the strain layer is a conductive film mainly made of carbon nanotubes and epoxidized natural rubber; the epoxidation degree of the epoxidized natural rubber is 30 to 50 mol%; The natural latex sponge layer comprises, by weight, 80 to 120 parts of natural latex, 2 to 5 parts of sulfur, 0.5 to 2 parts of 2-mercaptobenzothiazole, 0.2 to 1.5 parts of 2-mercaptobenzimidazole, 1 to 4 parts of potassium oleate, 2 to 5 parts of zinc oxide, 0.5 to 2 parts of potassium hydroxide and 0.5 to 2 parts of sodium fluorosilicate; The preparation process of the natural latex sponge layer is as follows: sulfur, 2-mercaptobenzothiazole, 2-mercaptobenzimidazole and potassium hydroxide dispersion are added to natural latex, and the mixture is aged to obtain a compound latex; the compound latex, potassium oleate, zinc oxide and sodium fluorosilicate are mixed to obtain a foamed latex; the foamed latex is injected into a mold, and the mold is shaped and vulcanized to prepare a natural latex sponge layer.
2. A sandwich pressure sensor according to claim 1, characterized in that: The carbon nanotubes are single-walled carbon nanotubes.
3. A method for preparing the sandwich pressure sensor according to any one of claims 1 to 2, characterized in that: The steps are: (1) After mixing the single-walled carbon nanotube dispersion and the epoxidized natural rubber latex, the mixture is shaken for 15 to 30 minutes and then injected into a mold to form a film to obtain a strain material, which is then spread on a natural latex sponge layer at a film-forming temperature of 40 to 65°C; (2) Paste the conductive copper foil on the surface of the strain material, inject and spread the foam latex on the conductive copper foil to seal the layer, then shape and vulcanize it, and dry it at 60°C for 2 to 2.5 hours to obtain a sandwich pressure sensor.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the single-walled carbon nanotube dispersion to the epoxidized natural rubber is 1:1 to 1:
100.
5. The preparation method according to claim 3 or 4, characterized in that: The concentration of the single-walled carbon nanotube dispersion is 1-4 mg / ml; the concentration of the epoxidized natural rubber latex is 100-350 mg / ml.
6. The preparation method according to claim 3, characterized in that: In the preparation process of the natural latex sponge layer, the aging temperature is 25°C and the time is 24 to 48 hours; the shaping temperature is 80 to 90°C and the time is 20 to 40 minutes; and the vulcanization temperature is 100°C and the time is 15 to 25 minutes.
7. The preparation method according to claim 3, characterized in that: The preparation process of the single-walled carbon nanotube dispersion is as follows: weigh single-walled carbon nanotubes and sodium taurodeoxycholate in a mass ratio of 1:7-10, mix with deionized water, and then place in an ice water bath for ultrasonic dispersion for 10-20 minutes, filter to remove undispersed carbon nanotubes, and then bottle for later use.
Citation Information
Patent Citations
Natural rubber modified Bucky paper, preparation method and application thereof, and sandwich structure strain sensor and application thereof
CN113405449A